(untitled) (Quest Journal of Management and Social Sciences, 2023)
Background: Employee remunerations and welfare packages naturally constitute the two major determinate factors that stimulate negative or positive reactions towards employee performance in an organisation. Objective: The study examines the effects of remuneration and welfare packages on employee performance in Nigerian public universities. Methodology: The researcher employed a mixed research method. A total of 100 questionnaires were administered to the academics and non-academic staff of the University of Ilorin and Kwara State University Malate through random sampling; hypotheses were tested using simple percentages and chi-square. Results: This menace has resulted in many negative effects, such as strikes, protests, corruption, dismal performance, slow development, side work, and nonchalant attitude, among other factors, within the staff of Nigerian public universities. Conclusion: Policies on remunerations should be reviewed, salaries and wages should be paid as when due; also, employees taking home pay should be capable of taking care of their needs, and welfare packages should be improved in order to improve employee performance for an effective, efficient and workable Nigeria public enterprises. Keywords: Remuneration, University, Welfare, Staff, Employee, Performance.